Immune Response, Inflammation, and the Clinical Spectrum of COVID-19 - García, Luis F. (Frontiers in Immunology, 2020)
The present COVID-19 pandemic was initiated in December 2019 in Wuhan (China) and rapidly extended to become a global sanitary and economic emergency. Its etiological agent is the coronavirus SARS-Cov-2. COVID-19 presents a wide spectrum of clinical manifestations, that go from an asymptomatic infection to a severe pneumonia accompanied by multisystemic failure leading to patient´s death. The immune response to SARS-CoV-2 is known to involve all the components of the immune system that all together appear responsible for viral elimination and recovery from the Infection. Nonetheless, such immune responses are implicated in the progress of the disease to a more severe and lethal process. This review describes the general aspects of both COVID-19, and its etiological agent SARS-CoV-2, stressing the similarities with other severe coronavirus infections, such SARS and MERS, but more importantly, pointing towards the evidences supporting the hypothesis that the clinical spectrum of COVID-19 is the consequence of the corresponding variable spectrum of the immune responses to the virus. The critical point where progression of the disease ensues appears to center in loss of the immune regulation between a protective response and an altered response due to exacerbation of the inflammatory component. Finally, it appears possible to delineate certain major challenges that should be intensively investigated to further understand COVID-19 immunopathogenesis, thus helping to design more effective diagnostic, therapeutic and prophylactic strategies